Sleep disturbances in nurse managers during the early and late stages of the COVID-19 pandemic - Boned-Galán, Ángel; López-Ibort, Nieves; Gascón-Catalán, Ana (Frontiers in Psychology, 2022)
Introduction Working conditions during the COVID-19 pandemic have affected health professionals’ quality of sleep. To date, most of the studies that assess the impact of the COVID-19 pandemic on sleep have been carried out with front-line health personnel, and almost none of them have been carried out with managers. Objective To evaluate the quality of sleep and the level of stress in nurse managers during the early and late stages of the COVID-19 pandemic. Methods Cross-sectional studies were carried out at two time points: after the lockdown period (July 2020) and a year and a half after the start of the pandemic (October 2021). A total of 102 nurse managers of a tertiary hospital were invited to participate. The Perceived Stress Scale (PSS-14) and Pittsburgh Sleep Quality Index (PSQI) were administered to assess stress levels and sleep quality. Results The response rate was 85.2% in 2020 and 81.3% in 2021. Nursing managers showed alterations in sleep quality throughout the pandemic: 70.1% after confinement and 61.4% at the beginning of the second wave. In addition to stress, the fear of contagion by COVID-19 influenced sleep problems. More than a year after the start of the pandemic, the professionals’ fear of contagion decreased. Perceived stress also decreased, but sleep disturbances remained. Conclusion High stress and poor sleep quality among nurse managers require special attention, and specific interventions need to be implemented. Hospitals should develop programs that help nurse managers develop skills to mitigate stress levels and thus improve sleep quality and professional quality of life.